Limited liability, asset price bubbles and the credit cycle: The role of monetary policy - Jakub Mateju (Charles University in Prague, Institute of Economic Studies (IES), 2015)
This paper suggests that non-fundamental component in asset prices is one of the drivers of financial and credit cycle. Presented model builds on the financial accelerator literature by including a stock market where limitedly-liable investors trade stocks of productive firms with stochastic productivities. Investors borrow funds from the banking sector and can go bankrupt. Their limited liability induces a moral hazard problem which shifts demand for risk and drives prices of risky assets above fundamental value. Embedding the contracting problem in a New Keynesian general equilibrium framework, the model shows that loose monetary policy induces loose credit conditions and leads to a rise in both fundamental and nonfundamental components of stock prices. Positive shock to non-fundamental component triggers a financial cycle: collateral values rise, lending rate and default rate decreases. These effects reverse after several quarters, inducing a credit crunch. The credit boom lasts only while stock market growth maintains sufficient momentum. However, monetary policy does not reduce volatility of inflation and output gap by reacting to asset prices.
Keywords: E32; E44; E52; G10; 330; credit cycle; limited liability; non-fundamental asset pricing; collateral value; monetary policy